Identifikasi Sampah Laut pada Daerah Pesisir Pantai Suprau Distrik Maladum Mes Kota Sorong - Angelberta Ivona Tuturop; Melisa Ch. Masengi; Roger R. Tabalessy; Joelan Palemba; Melani Manurung (Fakultas Ilmu Pendidikan Universitas Pahlawan Tuanku Tambusai, 2025)
Coastal areas are areas that are greatly influenced by various human activities, both directly and indirectly. Activities that often have an impact on coastal areas are dumping waste into the sea. The purpose of this study was to identify the types of waste found in the coastal area of ​​Suprau Beach, Maladum Mes District, Sorong City. The method used in this study is to use the transect line method with identification techniques referring to UNEP 2009. Based on the research conducted, the results of the level of environmental pollution by marine waste are dominated by plastic waste with a percentage of the weight of the waste being 51% of the total waste found with the percentage of the type of waste that dominates, namely plastic waste of 63%. In addition to plastic waste, other types of waste that dominate also include organic waste such as wood, leaves which are categorized as other types of waste and types of glass, ceramic, styrofoam, and cardboard waste.